Diarylheptanoids with NO production inhibitory activity from Amomum kravanh. Issue 8 (15th April 2020) - Zhang, Jun-Sheng; Cao, Xin-Xin; Yu, Jin-Hai; Yu, Zhi-Pu; Zhang, Hua
Graphical abstract: Abstract: Seven new diarylheptanoids, kravanhols C−I (1 –7 ), along with two known analogues (8 and 9 ), were isolated from the fruits of Amomum kravanh . The structures of compounds 1 –7 were elucidated by analysis of spectroscopic data, and the absolute configurations of selective ones were determined by time-dependent density functional theory (TD-DFT) based electronic circular dichroism (ECD) calculations. All compounds were evaluated for their inhibitory effects on the nitric oxide (NO) production induced by lipopolysaccharide (LPS) in murine RAW264.7 macrophage cells. Compounds 2, 5, 6 and 9 exhibited moderate inhibitory activity with IC50 values in the range of 17.4–26.5 μM, being more potent than the positive control dexamethasone (IC50  = 32.5 μM).